2017
DOI: 10.1007/s00246-017-1768-5
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Ligation Versus Percutaneous Closure of Patent Ductus Arteriosus in Very Low-Weight Preterm Infants: Which are the Real Benefits of the Percutaneous Approach?

Abstract: Percutaneous treatment of patent ductus arteriosus (PDA) in extreme premature infants is technically difficult, and therefore, often not consider as an alternative to surgery. The main objective of our work was to compare respiratory status prior and post ductal closure and morbi-mortality, in our series of preterm infants with percutaneous PDA closure versus surgical ligation in the same time-period. Retrospective review of all premature infants submitted to percutaneous and surgical PDA closure from January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 47 publications
7
49
0
1
Order By: Relevance
“…Oversedation (especially with opioid infusions) is another potential contributing factor. It is also notable that prior research has found improved respiratory outcomes when comparing percutaneous to surgical interventions …”
Section: Discussionmentioning
confidence: 99%
“…Oversedation (especially with opioid infusions) is another potential contributing factor. It is also notable that prior research has found improved respiratory outcomes when comparing percutaneous to surgical interventions …”
Section: Discussionmentioning
confidence: 99%
“…Recent retrospective studies comparing percutaneous PDA closure versus surgical ligation showed that preterm infants with transcatheter PDA occlusion have faster improvement in respiratory function. 31,32 Patients undergoing surgical ligation at the same time period, and reportedly with similar characteristics, had higher overall morbidity including a high incidence of recurrent laryngeal nerve palsy (17%). The authors concluded that transcatheter closure of PDA in select low birth weight and preterm infants is a safe and reliable alternative to surgical ligation.…”
Section: Due To Limited Availability Of Alternative Devices In the Unmentioning
confidence: 97%
“…Though the transcatheter reported outcomes in preterm infants are promising, they have not been directly compared with surgical outcomes in prospective trials. Recent retrospective studies comparing percutaneous PDA closure versus surgical ligation showed that preterm infants with transcatheter PDA occlusion have faster improvement in respiratory function . Patients undergoing surgical ligation at the same time period, and reportedly with similar characteristics, had higher overall morbidity including a high incidence of recurrent laryngeal nerve palsy (17%).…”
Section: Transcatheter Pda Occlusion Techniques In Smaller Patients: mentioning
confidence: 99%
See 2 more Smart Citations